Multi-disciplinary capacity strengthening for food and nutrition policy analysis: lessons from Malawi - Babu, Suresh Chandra (1997)
Lack of sufficient analytical capacity in most of the developing countries in sub-Saharan Africa has been frequently suggested as a major factor in determining the appropriateness of food and nutrition policy interventions. This paper documents an approach implemented in Malawi for the past seven years to develop multidisciplinary capacity to analyse food and nutrition policies and programmes. A conceptual framework for identifying the areas of capacity-strengthening in food and nutrition planning and policy analysis is developed. Generalizable lessons from the Malawi experience are presented. Various issues that relate to enhancing the efficiency of capacity-strengthening programmes in sub-Saharan Africa are addressed. It is argued that continuous dialogue between food and nutrition researchers and policy decision makers and between the trainers in academic institutions and donor agencies is fundamental for achieving the goals of improved capacity for food and nutrition policy analysis.